The Effect of Business Incubator Graduation Policy towards the Performance of Entrepreneurs in the Early Start-Up Companies in Malaysia with the Moderating Effect of Risk-taking Propensity - Jimainal, Mohd Noor Hidayat; Hassan, Ramraini Ali; Kalimin, Khairiah Mazdiah; Ansar, Rudy; Chekima, Brahim; Fook, Lim Ming (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The objective of this study is to investigate the impact of business incubator graduation policy on the performance of entrepreneurs in the early start-up companies in Malaysia with the moderating role of risk-taking propensity. The target respondents were entrepreneurs who graduated from business incubator in Sabah, Sarawak, Johor, Selangor, Kuala Lumpur and Penang. A total of 121 valid questionnaires were used for analysis in this paper. The data were analysed using Partial Least Squares (PLS) within the Structural Equation Modelling (SEM) technique. The results show that graduation policy has a significant positive effect on the performance of entrepreneurs in the early start-up companies. However, risk-taking propensity has no moderating role between graduation policy and the performance of entrepreneurs in the early start-up companies in Malaysia. The findings of the study’s outputs may serve as guidelines for the Malaysian policy makers and government agencies as well as business incubators to have a better picture of entrepreneurs in business incubators in Malaysia. The results obtained can also be used by other researchers as guidelines for their future research in the same field of study. Discussion and limitation of the study is elaborated further.